Risk analysis factors of the emission in transportation a case study - Dubai taxi - Al Ali, Yousif; Al Kattan, Ibrahim; Hrairi, Meftah (2010)
Increasing number of traditional vehicles threaten the economical development, pollutes our air and creating environmental hazards. Urban areas in UAE are currently facing growing traffic congestion by rising air pollution as a result of vast growth of population and consequently number of vehicles in the last twenty years. The spotlight of this study is to identify the critical risk factors that can be used to assess the impact of transportation emission on overall environmental risk. In this study risk analysis factors in transportation system focuses on Dubai Taxi fleet as a case study. The most critical emission levels are from; Carbon monoxide (CO), Nitrogen oxide (NOx) and Hydrocarbons (HC), which will be analyzed. The objective is to develop a sustainable transportation planning will help to solve this problem. The approach is based on a comprehensive assessment to address the negative effect of the vehicles on the environment at different period of times. The research considers different solution for the pollution problem by using a proposed model to evaluate and test its effectiveness within the international standard of air emission regardless of the vehicles or population growth in the future.